Indicadores considerados por professores para a detecção de abuso sexual infantil - Boscardin, Marina Kayser (2018)
The present Master's thesis consists of two studies, one theoretical and one empirical, on the indicators that preschool teachers consider for the detection of child sexual abuse (CSA). The theoretical section consisted of a systematic review of the literature, with the objective of identifying the teachers' knowledge about CSA. More specifically, the study sought to identify which indicators presented by children that teachers consider to be suggestive of CSA. The empirical section consisted of an experiment that aimed to verify if a drawing with a potentially interpretive element as a male genital organ would influence the detection rate of the teachers in a suspicious case. To do so, participants were exposed to the vignette of a fictitious case, which varied depending on the presentation form of the suggestive drawing. After exposure to the vignette participants responded if they detected CSA, which indicators of the vignette led them to detection, and which indicators generally they considered characteristic of CSA. The initial hypothesis of the study was that the detection rates would be higher in the group exposed to the vignette which contained, in addition to the suggestive drawing, other indicators suggestive of CSA. Although the results confirmed the initial hypothesis, it was verified that there was a greater increase in the detection rates with the simple addition of the suggestive drawing. These results reinforce the importance of specific training for teachers to guide them on the best practices to be adopted in the face of suspected CSA. In this sense, it is fundamental to guide them that detection is not based on an isolated indicator, but rather on a set of indicators and that these are properly contextualized. It is also recommended that, upon detection, the case be referred to the competent bodies, as it is not the responsibility of the teachers to investigate the CSA.